The Effect of Green Tea Leaf Decoction on Changes in Cholesterol Levels in the Elderly in Losari Village, Gondang District, Nganjuk Regency - Lexy Oktora Wilda; Ine Nadia Damayanti (Journal of Global Research in Public Health, 2023)
Complex changes in the elderly often cause health problems, one of which is an increase in blood cholesterol levels. Total cholesterol in the blood increases with the aging process. Cholesterol is a form of fat that the body needs. Cholesterol can cause problems if the levels are excessive. The purpose of this study was to determine the effect of giving green tea leaf decoction to changes in cholesterol levels in Losari Village, Gondang District, Nganjuk Regency as many as 26 respondents. The results of this study indicate that the cholesterol levels before being given the decoction of green tea leaves are mostly in the high cholesterol category, namely 15 respondents (58%) and the cholesterol levels after being given the decoction of green tea leaves, half have the category of normal cholesterol levels, namely 13 respondents (50%). sufficient, namely 13 respondents (50%). Wilcoxon test results show that p value = 0.001 ≤ α = 0.05. so that Ha is accepted, meaning that there is an effect of giving green tea leaf decoction to changes in cholesterol levels in the elderly in Losari Village, Gondang District, Nganjuk Regency.